Glycolysis - energy and useful cell chemicals - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Overview of metabolism, Interconnections of glycolysis and other metabolisms, Glycolysis in detail
Reviewed at 2022/11/27